2008
DOI: 10.1021/es071719a
|View full text |Cite
|
Sign up to set email alerts
|

Exergy: Its Potential and Limitations in Environmental Science and Technology

Abstract: New technologies, either renewables-based or not, are confronted with both economic and technical constraints. Their development takes advantage of considering the basic laws of economics and thermodynamics. With respect to the latter, the exergy concept pops up. Although its fundamentals, that is, the Second Law of Thermodynamics, were already established in the 1800s, it is only in the last years that the exergy concept has gained a more widespread interest in process analysis, typically employed to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
156
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 282 publications
(159 citation statements)
references
References 131 publications
2
156
0
1
Order By: Relevance
“…EcoLCA quantifies ecological resource consumption using a hierarchy of thermodynamic metrics including energy, industrial cumulative exergy consumption (ICEC), and ecological cumulative exergy consumption (ECEC), as well as mass flow. However, while exergy-based methods for thermodynamic aggregation of natural resource consumption may provide useful insights, these methods have their own limitations and are debated in the literature [113][114][115][116][117][118][119][120]. Research on combining the best advantages of Process LCA and EIO-LCA has also resulted in Hybrid LCA approaches, which combine the details of Process LCA with the greater completeness of EIOLCA [121,122].…”
Section: Eio-lca and Hybrid Lcamentioning
confidence: 99%
“…EcoLCA quantifies ecological resource consumption using a hierarchy of thermodynamic metrics including energy, industrial cumulative exergy consumption (ICEC), and ecological cumulative exergy consumption (ECEC), as well as mass flow. However, while exergy-based methods for thermodynamic aggregation of natural resource consumption may provide useful insights, these methods have their own limitations and are debated in the literature [113][114][115][116][117][118][119][120]. Research on combining the best advantages of Process LCA and EIO-LCA has also resulted in Hybrid LCA approaches, which combine the details of Process LCA with the greater completeness of EIOLCA [121,122].…”
Section: Eio-lca and Hybrid Lcamentioning
confidence: 99%
“…In order to assess these new research directions, a group of researchers has mapped the current state of affairs in an overview article [27]. They distinguish four paths of development: ecosystem analysis, industrial system analysis, (thermo-)economic analysis based on extended exergy accounting (EEA) and environmental impact assessment, for example through the Cumulative Exergy Extraction from the Natural Environment (CEENE) approach.…”
Section: A Unification Theory?mentioning
confidence: 99%
“…They distinguish four paths of development: ecosystem analysis, industrial system analysis, (thermo-)economic analysis based on extended exergy accounting (EEA) and environmental impact assessment, for example through the Cumulative Exergy Extraction from the Natural Environment (CEENE) approach. The latter category aims at reconciling LCA, which is mainly focused on harmful emissions, with exergy by considering those negative environmental impacts in terms of their related exergy effects or through the exergetic cost of abating the emissions in case ( [27], pp. 2228-2229).…”
Section: A Unification Theory?mentioning
confidence: 99%
See 1 more Smart Citation
“…Others have suggested that LCA and exergy analysis complement each other (e.g., [40][41][42][43]. Exergy analysis can also be used as a stand-alone assessment tool, e.g., [29,[44][45][46][47], or linked to other environmental systems analysis tools, such as Strategic Environmental Assessment [48], besides its use as an engineering tool for analyzing and optimizing different types of processes [29,49]. This non-exhaustive list indicates that the applications of exergy analysis are numerous and that it is an established method in many areas.…”
mentioning
confidence: 99%